A global point prevalence survey of antimicrobial use in neonatal intensive care units: The no-more-antibiotics and resistance (NO-MAS-R) study. (February 2021) - Prusakov, Pavel; Goff, Debra A.; Wozniak, Phillip S.; Cassim, Azraa; Scipion, Catherine E.A.; Urzúa, Soledad; Ronchi, Andrea; Zeng, Lingkong; Ladipo-Ajayi, Oluwaseun; Aviles-Otero, Noelia; Udeigwe-Okeke, Chisom R.; Melamed, Rimma; et al.
Abstract: Background: Global assessment of antimicrobial agents prescribed to infants in the neonatal intensive care unit (NICU) may inform antimicrobial stewardship efforts. Methods: We conducted a one-day global point prevalence study of all antimicrobials provided to NICU infants. Demographic, clinical, and microbiologic data were obtained including NICU level, census, birth weight, gestational/chronologic age, diagnoses, antimicrobial therapy (reason for use; length of therapy), antimicrobial stewardship program (ASP), and 30-day in-hospital mortality. Findings: On July 1, 2019, 26% of infants (580/2, 265; range, 0–100%; median gestational age, 33 weeks; median birth weight, 1800 g) in 84 NICUs (51, high-income; 33, low-to-middle income) from 29 countries (14, high-income; 15, low-to-middle income) in five continents received ≥1 antimicrobial agent (92%, antibacterial; 19%, antifungal; 4%, antiviral). The most common reasons for antibiotic therapy were "rule-out" sepsis (32%) and "culture-negative" sepsis (16%) with ampicillin (40%), gentamicin (35%), amikacin (19%), vancomycin (15%), and meropenem (9%) used most frequently. For definitive treatment of presumed/confirmed infection, vancomycin (26%), amikacin (20%), and meropenem (16%) were the most prescribed agents. Length of therapy for culture-positive and "culture-negative" infections was 12 days (median; IQR, 8–14) and 7 days (median; IQR, 5–10), respectively. Mortality was 6% (42%, infection-related). An NICU ASP was associated with lower rate of antibiotic utilization ( p  = 0·02). Interpretation: Global NICU antibiotic use was frequent and prolonged regardless of culture results. NICU-specific ASPs were associated with lower antibiotic utilization rates, suggesting the need for their implementation worldwide. Funding: Merck & Co.; The Ohio State University College of Medicine Barnes Medical Student Research Scholarship